2010
DOI: 10.1074/jbc.m110.115121
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Variation among Bordetella

Abstract: The O chain polysaccharide (O PS) of Bordetella bronchiseptica and Bordetella parapertussis lipopolysaccharide is a homopolymer of 2,3-diacetamido-2,3-dideoxygalacturonic acid (GalNAc3NAcA) in which some of the sugars are present as uronamides. The terminal residue contains several unusual modifications. To date, two types of modification have been characterized, and a survey of numerous strains demonstrated that each contained one of these two modification types. Host antibody responses against the O PS are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Bordetella O-antigen types were previously defined as O1- or O2- serotype based on cross-reactive antigenicity [ 17 ], but recently it was shown that B. bronchiseptica strain MO149 produces a poorly immunogenic O-antigen designated O3 [ 14 ]. This O-antigen, unlike O1 and O2, was not recognized by antibodies generated during infection, and did not cross-react with any Bordetella O1- or O2- serotype specific antibodies [ 14 - 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bordetella O-antigen types were previously defined as O1- or O2- serotype based on cross-reactive antigenicity [ 17 ], but recently it was shown that B. bronchiseptica strain MO149 produces a poorly immunogenic O-antigen designated O3 [ 14 ]. This O-antigen, unlike O1 and O2, was not recognized by antibodies generated during infection, and did not cross-react with any Bordetella O1- or O2- serotype specific antibodies [ 14 - 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bordetella O-antigen types were previously defined as O1- or O2- serotype based on cross-reactive antigenicity [ 17 ], but recently it was shown that B. bronchiseptica strain MO149 produces a poorly immunogenic O-antigen designated O3 [ 14 ]. This O-antigen, unlike O1 and O2, was not recognized by antibodies generated during infection, and did not cross-react with any Bordetella O1- or O2- serotype specific antibodies [ 14 - 16 ]. To assess the diversity of O-antigen antigenicity among the classical bordetellae, we examined more strains by purifying their LPS and probing with antibodies generated against LPS containing either O1-, O2-, or O3-type O-antigens ( B. bronchiseptica strain RB50, B. bronchiseptica strain 1289, or B. bronchiseptica strain MO149, respectively) (Figure 1 A-C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations